Report of the Steering Committee on Art and Culture for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, Government of India, 2001)
The Steering Committee Report on Art & Culture for the Tenth Five-Year Plan (2002–2007) presents a comprehensive strategic framework for preserving, promoting, and strengthening India’s diverse cultural heritage within the broader context of national development. Recognizing culture as a foundational element of India’s pluralistic identity and social cohesion, the report builds upon achievements of earlier plans, including the establishment of Zonal Cultural Centres, Multipurpose Cultural Complexes, and the creation of the National Cultural Fund, as well as the internationally acclaimed conservation efforts of the Archaeological Survey of India. The Committee proposes a three-pronged approach focusing on preservation of archaeological and historical heritage, promotion of classical, folk, and tribal arts—particularly endangered oral traditions—and institutional development through modernization of museums, libraries, and enhanced digital documentation systems. Emphasizing greater coordination among cultural institutions, inter-agency collaboration, and private sector participation, the report advocates an expanded cultural policy framework that integrates community engagement and public awareness initiatives. With a substantially increased financial allocation of ₹2708.33 crores—nearly three times the previous outlay—the Tenth Plan seeks to create sustainable cultural infrastructure, broaden access to cultural resources, and position arts and heritage as integral components of India’s socio-economic progress.
Government of India Planning Commission October-2001
Keywords: Steering Committee on Art & Culture; Tenth Five-Year Plan (2002-2007); Cultural Heritage Preservation; Archaeological Survey of India; Zonal Cultural Centres; National Cultural Fund; Folk and Tribal Arts; Museums and Libraries; Cultural Infrastructure Development; Digital Documentation; Community Participation; Cultural Policy Framework